TAKING A STRATEGIC VIEW - Sulina Green (Social Work/Maatskaplike Werk, 2008)
This special issue of Social Work/Maatskaplike Werk appears on the eve of the 34th Congress ofthe International Association of Schools of Social Work (IASSW) to be held in Durban, SouthAfrica next month. As the main theme of the Congress is Transcending Global-Local Divides:Challenges for Social Work Education and Practice, this issue is intended to expose our readersto strategic thinking about social welfare issues with articles by some of the conferees as well asprominent researchers and practitioners in South Africa. The special issue introduces researchers’responses to challenges for social work during a period of socio-economic transformation